COST EFFICIENCY ANALYSIS AND RISK MANAGEMENT OF THE SELF-MANAGED BATCHING PLANT METHOD MUSI TOLL KAYU AGUNG-PALEMBANG-BETUNG BRIDGE PROJECT - Supriyono, Joko; Kristiawan, Agung; Ramadhani, Vicha Silviana; Suwandi, Putri Anggi Permata (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2026)
This study was conducted on the Musi Bridge Project of the Kayu Agung–Palembang–Betung Toll Road to determine the most efficient and controlled concrete supply method, considering the high proportion of concrete costs, potential distribution delays, and structural quality requirements in strategic infrastructure projects. The research aimed to compare the self-managed batching plant method and the ready-mix method in terms of cost efficiency, technical and non-technical risks, and concrete quality performance. A quantitative descriptive-comparative approach was applied using primary data from project documents, including cost summaries, material quantities and prices, job mix formulas, risk matrices, and quality testing reports, supported by field observations. The analysis involved cost calculations, risk scoring and categorization, and evaluation of compliance with technical specifications. The results show that the self-managed method achieved cost savings of 15.7% and lower risk levels compared to the ready-mix method, while both methods met structural quality requirements. Therefore, the study concludes that self-managed batching plants are more effective for large-scale projects when supported by adequate technical and operational capacity. Keywords: concrete supply method, self managed batching plant, ready-mix concrete, cost and risk analysis ;